Complications, Implications, and Prevention of Electrosurgical Injuries: Corner Stone of Diathermy Use for Junior Surgical Trainees - Siddaiah-Subramanya, Manjunath; Tiang, Kor Woi; Nyandowe, Masimba (The Surgery Journal, 2017)
Diathermy is commonly used in modern-day surgery. The incidence of electrosurgical injuries related to diathermy is under reported, as it is difficult to ascertain the true impact on both patient and healthcare professionals. As junior surgical trainees, understanding of the mechanism and biophysics of the electrosurgical tools enables safer usage and contributes to improved outcome. Careful use of electrosurgical tools during operation and appropriate communication amongst staff members are pivotal to a safe surgical outcome. Here, we discuss the causes and risk factors regarding electrosurgical complications along with suggestions to ensure safe practice, focusing on commonly neglected areas.
Keywords: diathermy; electrosurgery; prevention; surgical trainees